Why Optometrists Need to be Blogging - Lahey, Rhona; Martel, Cameron (Canadian Journal of Optometry, 2020)
We are huge proponents of blogging for Optometry practices. It has proven to be one of the most effective ways to generate new traffic, increase brand awareness, and attract new patients. That’s why we have made it one of the pillars of our SEO (search engine optimization) strategy.